Bioceramic Production from Sea Urchins - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2012)
Bioceramic nanopowders, currently one of the most demanding challenges for producing new biomaterials, have been tackled only when starting from chemical reagents. There are few studies aiming at producing hydroxyapatite nanopowders from naturally derived raw materials, such as nacre shells. Natural species of sea origin, such as corals and nacres, always attract special interest in biomaterials science and technology. Nacre shells are made up of pure aragonite crystallized in an organic matrix. The most common way to transform aragonite structures to hydroxyapatite is via hydrothermal transformation under very high pressure. However, such ways can be very dangerous if the equipment is worn. Ultrasonic and hotplate methods are apparently very safe. This work proposes a new approach for developing highly bioactive fine powders of Ca-phosphates (which can be used afterwards to build up hydroxyapatite-based bioceramic bone-scaffolds) from sea urchins via the above mentioned methods. The suspended raw powders were put on a hotplate (i.e. ultrasound). The temperature was set to 80 degrees C for 15 min and then, equivalent (to the amount of CaCO3 in the sea urchins) amount of H3PO4 was added drop by drop into the solution. The reaction continued for 2 h. Then, to evaporate the liquid part, the mixture was put into an incubator at 100 degrees C for 24 h and the resultant dried sediment was collected. X-ray diffraction analysis identified various calcium phosphate phases, predominantly monetite, and tricalcium phosphate as a secondary phase. The worldwide availability and the low cost of all kinds of nacre and sea urchin shells, along with their biological-natural origin are attractive features conferring to them a high potential for preparing calcium phosphate materials for uses in biomedicine. Heart urchin, used in this study, can be an ideal candidate for producing bioceramic particles.
Keywords: HYDROXYAPATITE COATINGS; CALCIUM ORTHOPHOSPHATES; MECHANICAL-PROPERTIES; TRICALCIUM PHOSPHATE; BONE IMPLANTS; CONVERSION